Ivermectin associated adverse events in the treatment and prevention of COVID-19 reported to the FACT pharmacovigilance project. (3rd August 2022) - Farah, Rita; Kazzi, Ziad; Brent, Jeffrey; Burkhart, Keith; Wax, Paul; Aldy, Kim
Abstract: Background: In August 2021, the Centers for Disease Control and Prevention (CDC) released a health alert following the rapid increase in ivermectin prescriptions and reports of severe illness associated with use of products containing ivermectin for the prevention or treatment of COVID-19 infections. The United States Food and Drug Administration (FDA) and the CDC have explicitly discouraged the use of ivermectin in the prevention or treatment of COVID-19 outside of clinical trials. The study aims to describe the adverse events (AEs) related to ivermectin use for the prevention or treatment of COVID-19. Methods: This is a prospective case series of adverse events related to therapeutics used in the prevention or treatment of COVID-19 submitted to the FDA ACMT COVID-19 ToxIC (FACT) Pharmacovigilance Project sub-registry between October 2020 and December 2021. This is an ongoing toxico-surveillance system at 15 major academic medical centers in 12 states. Data collected included sociodemographics, exposure related information including dose, frequency, route, duration, and reason for taking ivermectin as well as a clinical description of the adverse event and the outcome. Results: A total of 40 patients who developed AEs following ivermectin use were reported to FACT over 15 months. Self-medication with veterinary formulations were reported in 18/40 patients Thirty-three patients presented to emergency departments and nineteen patients were admitted to the hospital. Patients reported using ivermectin for prevention (24/40), treatment of symptoms (19/40), and for treatment of documented COVID-19 (8/40). Neurological toxicity was the most frequent finding. Fifteen patients had minor symptoms while 25 developed severe toxicity. Conclusions: Ivermectin use for the attempted treatment of COVID-19 has potential adverse health effects primarily related to neurological function. This is especially true when patients are self-treating with this medication and when they are using formulations intended for non-human use.